Capturing Beginning Teacher’s Emotional Experiences in Teaching: An Analysis of Teaching Case in Introduction to Literature Class - Aplonia Nelci Ke Lomi (Universitas Islam Sultan Agung, 2022)
Teachers frequently experience a wide variety of emotions during their teaching services. It is reported that the teachers ‘emotional experiences affect their performances in the classroom and can be one of the main sources of burnout and retention. This study captures the emotional experiences faced by a beginning teacher in her first days in the teaching practice program in an institution. This is a self-study with descriptive qualitative as the method of research. The researcher analyzed the teaching reflection as the instrument of the research. Based on the reflection, the teacher experienced emotional teaching practice mostly in dealing with the students’ behavior, discipline and engagement. She is also emotionally triggered in dealing with dissatisfaction and students’ effort in learning. Before pre-service teachers begin their teaching practice in schools, it is suggested that education study programs draw attention to this problem. Pre-service teachers must also comprehend the significance of reflective practices so that they can learn from their classroom performances and encounters. Future researchers are urged to investigate teachers’ emotional experiences in a broader context and with a greater number of participants.